Imitation and the development of infant learning, memory, and categorisation - Emily JH Jones; Jane S Herbert (Revue de Primatologie)
The ability to copy the actions of others is present from birth in both infant humans and chimpanzees and provides a method for the social transmission of knowledge. For this type of learning to have an impact over the long-term, the infant must be able to encode, store, and retrieve the information they receive for use at a later date. Here we review the literature with the deferred imitation paradigm to demonstrate that by at least 6 months of age, human infants are capable of these comparatively advanced cognitive abilities, which are thought to involve the declarative memory system and the hippocampal formation. Across early development there are dramatic changes in the duration over which information can be retained and the ability of infants to retrieve and express their memories in a flexible manner, which enables them to solve new problems. Research with the deferred imitation paradigm therefore provides important insight into our understanding of social and cognitive development as well as brain development.